BOOK REVIEWS. Issue 3 (July 2016) - Unknown
Abstract : Books reviewed in this issue Literature and Fine Arts Zalambani, Maria. L'istituzione del matrimonio in Tolstoj . Zhilyaev, Arseny, ed. Avant‐Garde Museology . Kunichika, Michael. "Our Native Antiquity": Archaeology and Aesthetics in the Culture of Russian Modernism . Rubins, Maria. Russian Montparnasse: Transnational Writing in Interwar Paris . Wozniuk, Vladimir. The Annotated WE: A New Translations of Evgeny Zamiatin's Novel . Lee, Steven S. The Ethnic Avant‐Garde: Minority Cultures and World Revolution . Tomoff, Kiril. Virtuosi Abroad: Soviet Music and Imperial Competition during the Early Cold War, 1945–1958 . Komaromi, Ann. Uncensored: Samizdat Novels and the Quest for Autonomy in Soviet Dissidence . Lutzkanova‐Vassileva, Albena. The Testimonies of Russian and American Postmodern Poetry: Reference, Trauma, and History . Lobenthal, Joel. Alla Osipenko: Beauty and Resistance in Soviet Ballet . Senelick, Laurence and Sergei Ostrovsky, eds. The Soviet Theater: A Documentary History . Dobrenko, Evgeny, and Mark Lipovetsky, eds. Russian Literature since 1991 . History Jaques, Susan. The Empress of Art: Catherine the Great and the Transformation of Russia . Schedewie, Franziska. Die Bühne Europas: Russische Diplomatie und Deutschlandpolitik in Weimar, 1798–1819 . Werth, Paul W. The Tsar's Foreign Faiths: Toleration and the Fate of Religious Freedom in Imperial Russia . Izmozik, V. C. "Chernye kabinety": Istoriia Rossiiskoi perliustratsii XVIII–nachalo XX veka . Wessel, Martin Schulze, and Frank E. Sysyn, eds. Religion, Nation, and Secularization in Ukraine . Buchen, Tim, and Malte Rolf, eds. Eliten im Vielvölkerreich: Imperiale Biographien in Russland und Österreich‐Ungarn (1850–1918) . Seleznev, F. A. Pervaia mirovaia voina: Vzgliad iz XXI veka: Rossiia i Nizhegorodskaia guberniia v 1914–1918 gg . Pearl, Deborah. Creating a Culture of Revolution: Workers and the Revolutionary Movement in Late Imperial Russia . Destivelle, Hyacinthe. The Moscow Council (1917–1918): The Creation of the Conciliar Institutions of the Russian Orthodox Church . Rieber, Alfred J. Stalin and the Struggle for Supremacy in Eurasia . Maisky, Ivan. The Maisky Diaries: Red Ambassador to the Court of St. James's, 1932–1943 . Kirschenbaum, Lisa A. International Communism and the Spanish Civil War: Solidarity and Suspicion . Kangaspuro, Markku, and Vesa Oittinen, eds. Discussing Stalinism: Problems and Approaches . Harrison, Richard W., ed. and trans. The Battle of Moscow, 1941–1942: The Red Army's Defensive Operations and Counteroffensive along the Moscow Strategic Direction . Gerovitch, Slava. Soviet Space Mythologies: Public Images, Private Memories, & the Making of a Cultural Identity . Vihavainen, Timo, and Elena Bogdanova, eds. Communism and Consumerism: The Soviet Alternative to the Affluent Society . Rupprecht, Tobias. Soviet Internationalism after Stalin: Interaction and Exchange between the USSR and Latin America during the Cold War . Plokhy, Serhii. The Gates of Europe: A History of Ukraine . Berger, Stefan, and Alexei Miller, eds. Nationalizing Empires . Mikhailov, N. V., and Jan Plamper, eds. Malen'kii chelovek i bol'shaia voina v istorii Rossii: Seredina XIX–seredina XX v . Social Sciences, Contemporary Russia, and Other Turoma, Sanna, and Maxim Waldstein, eds. Empire De/Centered: New Spatial Histories of Russia and the Soviet Union . Khanenko‐Friesen, Natalia. Ukrainian Otherlands: Diaspora, Homeland, and Folk Imagination in the Twentieth Century . Brusis, Martin, et al., eds. Politics and Legitimacy in Post‐Soviet Eurasia . Bystrova, A., A. Duka, and D. Tev, eds. Power and Elites . Dugin, Alexander. Eurasian Mission: An Introduction to Neo‐Eurasianism . Dugin, Alexander. The Fourth Political Theory . Gel'man, Vladimir. Authoritarian Russia: Analyzing Post‐Soviet Regime Changes . Stephenson, Svetlana. Gangs of Russia: From the Streets to the Corridors of Power . Wood, Elizabeth A., William E. Pomeranz, E. Wayne Merry, and Maxim Trudolyubov, eds. Roots of Russia's War in Ukraine . Lee, Rensselaer, and Artyom Lukin. Russia's Far East: New Dynamics in Asia Pacific and Beyond . Kanet, Roger E., and Matthew Sussex, eds. Power, Politics and Confrontation in Eurasia: Foreign Policy in a Contested Region .